Importance of Farm Environment to Shape Poultry-Related Microbiomes Throughout the Farm-to-Fork Continuum of Pasture-Raised Broiler Flocks - Rothrock, Michael J.; Locatelli, Aude (Frontiers in Sustainable Food Systems, 2019)
The poultry farm environment plays a key role in the microbial colonization of chickens during production, which shapes what enters the processing and final retail environments. The aim of this study was to evaluate the effect of the farm environment on the microbial composition of pasture-raised broilers using a combined cultural and microbiomic farm-to-fork. To achieve this, two nearby pastured poultry farms raised small flocks of Freedom Ranger broilers obtained from the same hatchery flock and fed the same diet throughout production. The major differences between the two farms were the physical farm environment, method of feather removal during processing (scalding versus skinning), and storage conditions of carcasses before customers received final product (refrigeration versus freezing). Microbiomes were compared from fecal and soil samples (live production), ceca (processing) and whole carcass rinses (processing, final product) to determine what effect the physical farm environment had on the poultry-related microbiomes. Overall, microbiomes in feces (p<0.04), soil (p<0.02) and ceca (p<0.02) samples from farm 1 harbored a higher taxonomic richness than farm 2. Beta-diversity analysis demonstrated significant differences between the broiler microbiomes of the two farms for samples collected at the live production (p < 0.04) and processing stages (p < 0.01), but not for final product carcass rinses. At the early live production stage ( 3 weeks old), fecal microbiomes from farm 1 were positively correlated to aluminum, iron, manganese, silicon and zinc concentrations in feces but not fecal microbiota from farm 2. At the late live production stage ( 12 weeks old), fecal microbiomes from both farms were no longer correlated to mineral content of feces but were negatively correlated to fecal pH. Given that the farm environment itself was the major difference, the results show that even when raising the same breed fed the same diet, poultry farms have their own ecology that shape the composition of the poultry-related microbiomes. Therefore, it is vital that future work focuses on elucidating the farm environmental variables that have the greatest influence on these microbiomes, thus allowing for eventual targeted interventions to better manage these microbial populations to benefit animal, environmental, and public health.